Macroeconomic indicators and systematic risk: is there a difference between emerging and developed markets? - Schlögl, Hubertus Tassilo (2018)
This explorative study is about the influencing effects of US macroeconomic announcements on changes in systematic risk with the focus on the difference between emerging and developed markets. Seven different US macroeconomic indicators have been examined and used to estimate betas as a proxy for the systematic risk around the announcement dates. In the period from 1996 until 2017, betas have been estimated over a three-month pre- and post window, resulting in 27 announcements per US macroeconomic indicator. The study also tries to provide insights of the consequences for portfolio managers, based on patterns of changes in betas and their relationship with changes in Sharpe ratios. The study results reveal that betas change consistently over the sample period, however, to a small magnitude. Also, the changes in mean Sharpe ratios around these announcement dates have not been found as statistical significant. However, the study results indicate that there is a positive relationship between changes in Sharpe ratios and changes in betas for developed countries as the Pearson correlation coefficient illustrates.